Factors That Affect Stock Prices At The Manufacturing Companies Listed On The Indonesia Stock Exchange - Siti Nurlaela, Yunita Setya Purwaningtyastuti, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study examined the influence of liquidity (Current Ratio), profitability (Net ProfitMargin, Earning Per Share, Return On Equity), solvency (Debt to Equity Ratio) against thestock price at manufacturing companies listed on the Indonesia stock exchange. Thepopulation of this research is all the manufacturing companies listed on the Indonesia stockexchange. The sample of this research as much as 84 manufacturing companies listed onthe Indonesia stock exchange. Types of data used are secondary data derived from theIndonesia Capital Market Directory (ICMD). Results descriptive statistics shows that anincrease in the stock price, which if viewed from the parameters of the stock price moredone on the parameters of the Earning Per Share. Based on the correlation analysis showsthe current ratio of negative effect variables significantly to the stock price, the Net ProfitMargin effect significantly to stock prices, Debt to Equity Ratio of significant negativeeffect against the share price, While Earning Per Share and Return On Equity did not affectstock prices. Based on regression analysis, we find that variable Current Ratio, Net ProfitMargin, Earning Per Share, Return On Equity, Debt to Equity Ratio effect significantly tostock prices.Keywords : Liquidity; Profitability; Solvency; the Stock Price.